Participation of a consortium in the procedure for the award of public contract with the examples of Poland, United Kingdom and France - Czerwiński, Marcin (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
The aim of the study is to compare regulations relating to consortia applying for public contracts in Polish, British and French law. Although it is impossible to find a common definition of a “consortium” for all EU members, due to the harmonization of rules concerning the functioning of the public procurement markets, the solutions adopted by member states are quite similar. However, there are also some specific regulations in individual countries. It is worth considering the usefulness of the adoption of similar solutions in other countries. In each analyzed country the author describes the general legal aspects of the functioning of a consortium in the legal system, then refers to similar legal institutions e.g. partnerships or subcontracting, and finally characterizes the regulation relating to the participation of the consortium in the procedure for the award of public contract.